Determination of N-methylcarbamates in foods - Borkovcová, I; Janoušková, Eva; Řehůřková, I; Ruprich, Jiří (Central European Journal of Public Health, 2004)
The multiresidue method using multisolvent extraction, SPE cleanup of the extract, HPLC with the use of OPA post-column reaction and fluorescence detection for the determination of N-methylcarbamate pesticides in food products was used. A matrix solid phase dispersion method of the isolation and extraction of carbamates was alternatively applied. In the introductory study 44 items of the food basket for the Czech Republic were analysed. In the major part of the studied samples, the considerable part of which was culinary treated, the concentration of the target carbamates was below the limit of the used detection method. In the concentration range of 10–100 μg/kg in the analysed samples of the studied analytes, aldicarb and its metabolites, e.g. methomyl and methiocarb were being found most frequently.
Keywords: In Vitro Techniques; vysokoúčinná kapalinová chromatografie; Agrochemicals; agrochemikálie; kontaminace potravin; techniky in vitro; Chromatography, High Pressure Liquid; Food Inspection; chemické techniky analytické; kontrola potravin; HERBICIDY KARBAMÁTOVÉ; Food Contamination; Chemistry Techniques, Analytical